2021
DOI: 10.1002/ps.6600
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis and regulatory mechanisms underlying fungal insecticides' resistance to solar ultraviolet irradiation

Abstract: Resistance to solar ultraviolet (UV) irradiation is crucial for field‐persistent control efficacies of fungal formulations against arthropod pests, because their active ingredients are formulated conidia very sensitive to solar UV wavelengths. This review seeks to summarize advances in studies aiming to quantify, understand and improve conidial UV resistance. One focus of studies has been on the many sets of genes that have been revealed in the postgenomic era to contribute to or mediate UV resistance in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 159 publications
(190 reference statements)
2
49
0
Order By: Relevance
“…The Cre1-mediated CCR is of special interest for insect-pathogenic fungi, which utilize scant nutrients in host integument during hyphal invasion into host body, serve as sources of environment-friendly insecticides and are represented best by Beauveria bassiana and the Metarhizium anisopliae complex [31][32][33]. Previously, a role of CRR1 (homologous to Cre1) was noted in the carbon regulation of the cuticle-degrading protease Pr1 in M. anisopliae [34].…”
Section: Introductionmentioning
confidence: 99%
“…The Cre1-mediated CCR is of special interest for insect-pathogenic fungi, which utilize scant nutrients in host integument during hyphal invasion into host body, serve as sources of environment-friendly insecticides and are represented best by Beauveria bassiana and the Metarhizium anisopliae complex [31][32][33]. Previously, a role of CRR1 (homologous to Cre1) was noted in the carbon regulation of the cuticle-degrading protease Pr1 in M. anisopliae [34].…”
Section: Introductionmentioning
confidence: 99%
“…The differences in both phenotypic and transcriptomic changes between Δ cfp1 and Δ cfp hint that M. robertsii and B. bassiana are distinctive in genetic background and regulatory mechanisms underlying lifecycle in vitro and in vivo. Such differences have also been revealed in the previous analysis of the master transcription factor Msn2 in the two fungi [ 37 ] and in the reviews on fungal adaptation to insect-pathogenic lifecycle and host habitats [ 8 , 9 , 10 , 38 , 39 ]. The differences could be likely due to different evolutionary histories of their insect pathogenic lifestyles [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 65%
“…Several studies have demonstrated the antibacterial activity of BSF larvae against numerous pathogens, such as S. aureus , S. epidermidis , B. subtilis , and methicillin-resistant S. aureus , due to the presence of several haemolymphatic peptides as well as antimicrobial peptides in BSF [ 18 ]. UV induction enhances the BSF antimicrobial activity, mainly due to UV induction’s biological effect, which induces changes in DNA expression [ 19 ]. Furthermore, the formation of thymine dimers between BSF DNA duplexes and adjacent inter-thymidine dimers on the same strand by UV treatment prevents normal base pairing and incorrect replication [ 20 ].…”
Section: Resultsmentioning
confidence: 99%